Assessing standard costs in local public bus transport: A hybrid cost model. (February 2018) - Avenali, Alessandro; Boitani, Andrea; Catalano, Giuseppe; D'Alfonso, Tiziana; Matteucci, Giorgio
Abstract: We develop a hybrid cost model for the determination of unit standard costs in the Italian local public bus transport sector. Detailed economic and transport data have been collected from companies producing more than 500 million of bus-kilometers in Italy observed in 2011. We draw upon the Bottom-Up approach for the estimation of the cost of the driving personnel and the economic cost of the rolling stock which usually cover more than 50% of the total economic cost. We thus adjust for efficiency the number of bus-kilometers per vehicle and the number of net driving hours per driver, which are characterized by very different levels of efficiency across Italian Regions. We resort to the Top-Down approach for the estimation of other costs. We find that an increase in the number of net driving hours per driver produces higher savings in urban services than intercity services. Conversely, the impact of an increase in the number of bus-kilometers per vehicle in the case of urban services is almost equal to that in the case of intercity services. The applied model allows us to tune the required level of efficiency according to regional desiderata. Our results might then be useful in order to define the maximum economic compensation that can be required by any local public transport firm which takes part in competitive tendering procedures for the allotment of service concessions or which is entitled with monopoly rights by political choice and/or local public ownership.